Despinning and shape evolution of Saturn's moon Iapetus triggered by a giant impact - Kuchta, M.; Tobie, G.; Miljkovic, Katarina; Behounková, M.; Soucek, O.; Choblet, G.; Cadek, O. (Academic Press Inc., 2015)
© 2015 Elsevier Inc. Iapetus possesses two spectacular characteristics: (i) a high equatorial ridge which is unique in the Solar System and (ii) a large flattening (. a-. c=. 34. km) inconsistent with its current spin rate. These two main characteristics have probably been acquired in Iapetus' early past as a consequence of coupled interior-rotation evolution. Previous models have suggested that rapid despinning may result either from enhanced internal dissipation due to short-lived radioactive elements or from interactions with a sub-satellite resulting from a giant impact. For the ridge formation, different exogenic and endogenic hypotheses have also been proposed, but most of the proposed scenarios have not been tested numerically. In order to model simultaneously internal heat transfer, tidal despinning and shape evolution, we have developed a two-dimensional axisymmetric thermal convection code with a deformable surface boundary, coupled with a viscoelastic code for tidal dissipation. The model includes centrifugal and buoyancy forces, a composite non-linear viscous rheology as well as an Andrade rheology for the dissipative part. By considering realistic rheological properties and by exploring various grain size values, we show that, in the absence of additional external interactions, despinning of a fast rotating Iapetus is impossible even for warm initial conditions (T>250. K). Alternatively, the impact of a single body with a radius of 250-350. km at a velocity of 2. km/s may be sufficient to slow down the rotation from a period of 6-10. h to more than 30. h. By combining despinning due to internal dissipation and an abrupt change of rotation due to a giant impact, we determined the parameters leading to a complete despinning and we computed the corresponding shape evolution. We show that stresses arising from shape change affect the viscosity structure by enhancing dislocation creep and can lead to the formation of a large-scale ridge at the equator as a result of rapid rotation change for initial rotation periods of 6. h.